Meing Handicraft Division at Lamalerans Traditional Fishing Boats - Blajan Konradus; Lasarus Jehamat; Yosef E. Jelahut; Aris Lambe (International Journal of Southeast Asian Studies (IJSAS), 2022)
Traditional fishermen in Lamalera have had a tradition of whaling for a long time, passed down from generation to generation. Whaling in the Lamalera tradition has a socio-cultural context. Thus, whaling is not only seen in a subsistence-economic framework, but in terms of certain cultures and traditions. Within that framework, whaling has a certain system that fishermen have been building for a long time. The Meing division of labor is one of the many subsystems in whaling. In practical terms, the success of whaling is highly dependent on the Meing's readiness to carry out his duties and roles on the boat. This division of roles shows that every element on board, regardless of shape and model, contributes to the success of whaling.